Three-dimensional numerical study of thickness effect on plastic CTOD and monotonic plastic zone in an aluminium CT specimen - Camas-Peña, Daniel; Branco, Ricardo; Antunes, Fernando Ventura; Neto, Diogo Mariano (Elsevier, 2023)
This work is a numerical study of CT specimens with straight cracks and different thickness values submitted to different load levels, which aims to analyse the shape and dimension variations of the monotonic yielded area near the crack tip, examining the impact of variables such as load magnitude, thickness of the specimen and position along the crack front. Additionally, it intends to explore the correlation between the size of the monotonic plastic zone and the plastic CTOD (Crack Tip Opening Displacement) to determine if a well-defined relationship exists. Furthermore, the impact of specimen thickness and load level on plastic CTOD will be explored. A complex plastic zone was found along the crack front, with the maximum area positioned at some distance from the crack front. A plane stress scale was determined considering the size of the equivalent bi-dimensional yielded area. When examining the behaviour across the thickness, no conclusive correlation was identified between the plastic CTOD and the monotonic yielded area. This suggests that utilising this parameter may not be appropriate for studies related to fatigue crack growth. However, when considering average values, a good correlation was found. The increase in thickness decreased the plastic CTOD values at the surface, while the interior values were unaffected.
Keywords: Ciencia de los materiales; Finite element analysis; Plane stress degree; plastic CTOD; Plastic zone size